Forecasting Energy Market Contracts by Ambit Processes: Empirical Study and Numerical Results. (28th October 2014) - Di Persio, Luca; Marchesan, Michele
Abstract : In the present paper we exploit the theory of ambit processes to develop a model which is able to effectively forecast prices of forward contracts written on the Italian energy market. Both short-term and medium-term scenarios are considered and proper calibration procedures as well as related numerical results are provided showing a high grade of accuracy in the obtained approximations when compared with empirical time series of interest.